2012
DOI: 10.1097/qai.0b013e31825c3a68
|View full text |Cite
|
Sign up to set email alerts
|

Adipogenic/Lipid, Inflammatory, and Mitochondrial Parameters in Subcutaneous Adipose Tissue of Untreated HIV-1–Infected Long-Term Nonprogressors

Abstract: Adipose tissue from untreated LTNPs may have limited but significant derangements in some adipogenic/lipid and may have inflammatory processes at a lower degree than that observed in untreated TPs. LTNPs may have mitochondrial-related alterations in adipose tissue which are greater than that observed in TPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
0
18
0
2
Order By: Relevance
“…PPARγ positively regulates these genes, indicating that HIV-1 infection per se induces adipose defects via PPARγ repression, consistent with a Vpr effect. Similar gene expression defects occur in fat tissues of HIV-infected, untreated long-term nonprogressors (10) and in mice expressing a 7.7-kb HIV-1 construct (30). …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…PPARγ positively regulates these genes, indicating that HIV-1 infection per se induces adipose defects via PPARγ repression, consistent with a Vpr effect. Similar gene expression defects occur in fat tissues of HIV-infected, untreated long-term nonprogressors (10) and in mice expressing a 7.7-kb HIV-1 construct (30). …”
Section: Discussionmentioning
confidence: 84%
“…Antiretroviral therapy (ART) drugs have been implicated in some abnormalities (4). However, adverse effects of ART cannot explain key aspects of the phenotype (5); for example, hypertriglyceridemia was noted before the ART era (6), and decreased body fat (7), altered fat distribution (8), and abnormal adipose gene expression (9, 10) occur in untreated patients. Thus, HIV-1 per se could cause adipose dysfunction and associated metabolic defects.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, adipose tissue is a potential HIV reservoir, leading to recruitment of T lymphocytes and macrophages into adipose tissue. [40] HIV also alters adipocyte differentiation[51, 41, 52]. One proposed mechanisms for this is inhibition of peroxisome proliferator-activated receptor-γ (a regulator of adipogenesis, lipogenesis, insulin sensitivity and normal cytokine/adipokine expression) target gene expression and activation of glucocorticoid target gene expression by the HIV protein Vpr, leading to accelerated lipolysis, increased macrophage infiltration into adipose tissue, diminished white adipose tissue quantity and hepatic steatosis[41].…”
Section: Consequences Of Obesity and Visceral Adipositymentioning
confidence: 99%
“…Additionally, a study of more than 80,000 veterans (27,000 PLWH) found that, after adjusting for Framingham risk, comorbidities, and substance use, PLWH had a 50% increased risk of an acute myocardial infarction (Freiberg et al, 2013). Current dominant hypotheses link the increased incidence of comorbidities to HIV-related chronic inflammation, adipose tissue abnormalities, and modifiable lifestyle factors (e.g., increased tobacco use and decreased physical activity; High et al, 2012; Vidal et al, 2012). Exercise can help prevent and/or mitigate the severity of these chronic comorbidities by improving insulin sensitivity, decreasing visceral fat, mitigating the inflammatory response and oxidative stress, increasing endothelial function, and optimizing lipid profiles (Hand, Lyerly, Jaggers, & Dudgeon, 2009; Kokkinos & Myers, 2010; Kruk, 2007; Roberts & Barnard, 2005; Yahiaoui, McGough, & Voss, 2012).…”
mentioning
confidence: 99%